Traumatic loss of maxillary central incisor: An orthodontic treatment approach - Rao, Sushmita B; Shetty, Vikram; Manasawala, Taher (Hasanuddin University, 2025)
Maxillary Incisors are most prone to trauma during childhood and many cases are left untreated until the growth is completed. Maxillary Incisor avulsion is considered as one of the most serious forms of trauma and immediate treatment is indicated whenever possible. This was a case of avulsion of Maxillary Central Incisor in a 13-year-old male patient and a delay in treatment which had cause mesial drifting of the adjacent teeth along with mandibular incisor extrusion leading to formation of deepbite. Fixed Orthodontic treatment was carried out and the space for replacement of the missing maxillary central incisor was maintained using a removable partial denture followed by placement of a single tooth implant after growth completion.